PENDUGAAN PERUBAHAN CADANGAN KARBON DI TAMBLING WILDLIFE NATURE CONSERVATION TAMAN NASIONAL BUKIT BARISAN SELATAN - Arief Prasetyo; Agus Hikmat; Lilik Budi Prasetyo (Media Konservasi, 2011)
Global warming effect can be mitigated in two ways, namely carbon loss reduction or emission and increasing carbon storage within vegetation. Forest can absorb CO2 trough photosynthesis process and sink them in biomass. Tambling Wildlife Nature Conservation (TWNC) as a part of Bukit Barisan Selatan National Park (BBSNP) have been facing land cover change due to encroachment. The study aimed to measure carbon stocks in various land cover and to compare carbon stocks for the whole are of TWNC TNBBS in 2000-2009. Carbon stocks measurement was conducted in TWNC TNBBS during August 8th to October 8th 2009, 50 plots were sampled including nature forest, secondary forest, agroforestry, shrub, Imperata cylindrica , and grassland by purposive sampling method. Soil carbon was not measured in this study. Nature forest has the highest carbon stocks by 178,44 MgC.ha-1, and grassland be a poorest carbon stocks (1,47 MgC.ha-1). During the time between 2000 to 2009,  primary forest carbon stock  decrease in amount of 457,792.52 Mg  along with the decrease in land cover of this forest type. As many as 24.4% of natural forests in 2000 turned into the others type of land use such as a secondary forest of  21.63%, for shrubs 1.61% and  0.06% for agroforestry in 2009. Totally, TWNC TNBBS has loss its carbon stocks as many as 279422 Mg, it’s mean the annual average carbon stocks contained in the TWNC TNBBS area decreased by around 27,942.2 Mg (0.72%) per year. Its mean, 1,024,547 Mg CO2 or 102,454.7 Mg CO2 every year was lose from TWNC TNBBS area. Keywords: biomass, carbon stock, emission, forest